The effectiveness of combined anaerob (pieces of brick, gravel and sand media) and aerob (coconut fibers and charcoal media) biofilters in reducing BOD5 and COD in the butchery liquid waste - Fitriana Sinaga; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Thebutchery liquid waste is rich in BOD5andCOD and it need to be processed before being flown to the environment. To understand the effectiveness of combined anaerob-aerob biofilters in reducing the BOD5and COD in the butchery liquid waste , a study was conducted in February - March 2018. The anaerob tanks were completed with pieces of brick, gravel and sand media (60 cm height), while that of the aerob was completed with coconut fibers and charcoal media (40 cm height). Around 215 L waste was kept in the anaerob tanks for 12 days and then it was flown to the aerob tanks and was kept for 10 days. Samplings for water quality parameters (BOD5, COD, DO and pH) was conducted 2 times, before the waste was processed and by the end of the experiment. The processed waste was then used for rearing Spirulinasp, 100 ml of Spirulina stock (104 cells/ ml) were reared in 1 liter of processed waste. Spirulina density was checked everyday. Results shown that the BOD5 reduced, from 1,307 mg/L to 113 mg/L(the effectiveness was 91.35 %); COD reduced, from 7,430 mg/L to 182 mg/L ( the effectiveness was 97,55 %); DO improved (from 1 mg/L to 5 mg/L) and pH also increased, from 6 to 8. The Spirulina density peaked by the 7th day, it was 4,074,666 cells/ml. Based on data obtained, it can be concluded that the use of anaerob-aerob biofilter was effective in improving the butchery waste water quality. Keywords : Organic waste, Anaerob tanks, Aerob tanks, Spirulina sp.